Letramento científico no âmbito do programa de iniciação à docência (PIBID): uma análise de produção científica na área de ensino de ciências - Silva, Cristiane Reis Barcelos (2016)
The Scientific Literacy is an educational proposition of science studies that aims to contribute to the training of citizens able to understand and use critically the basic scientific concepts in their social context. Thus, a science education aimed literate scientifically to the individuals, can not be reduced to mere transmission of content, however, should favor beyond the understanding of terms and scientific concepts, the understanding the nature of science and social-scientific issues, which implies in teacher training and the development of teaching skills to work this perspective in basic education. It is in this context of scientific literacy in teacher training, which fall within the theme of this research and aim to analyze in scientific production of science teaching area, such as the proposed Scientific literacy is addressed in the Institutional Scholarship Program for Introduction to Teaching (PIBID). We began this documentary research with a literature on the topics "Scientific Literacy" and "Scientific Literacy in Science Teacher Education." Through this mapping selected for the composition of our corpus of analysis all studies were addressed to the relation "Scientific Literacy and PIBID". For the analysis of textual productions we used the technique Discursive Textual Analysis. Four categories were identified in the Scientific Literacy and addressed in the textual productions on PIBID: the first is the groups and their purposes; the second encompasses the knowledge involved in this process; the third, it discusses educational proposals developed in basic education for this purpose; and the fourth, we have features of teacher training activities in this perspective. We have found, through the analysis of production, the sub-projects PIBID, which work's focus is the Scientific Literacy, have contributed to the training of teachers who are knowledgeable about this goal of science education and seek to overcome the teaching focused only on contents, proposing scientific research activities, discussions on relations between science, technology, society and environment, and the use of scientific language.